Determining writing genre: towards a rubric-based approach to automated essay grading - Lam, Hon; Dillon, Tharam; Chang, Elizabeth (IEEE, 2011)
A writing genre can be thought of as the style in which the writer chooses to present textual content to the reader. We distinguish four main types of essay genres namely Narrative, Persuasive, Descriptive and Expository. An essay’s writing genre can be identified by searching for salient features present within those genres using various Natural Language Processing tools such as Named Entity Recognition, Part of Speech tagging and Sentence Parsing. This paper explains the more common writing genres in student essays and describes the method in which essays in the narrative genre are identified.